The daily management of athletes with diabetes - MacKnight, J. M.; Mistry, D. J.; Green Pastors, J.; Holmes, V.; Rynders, C. A. (Clinics in Sports Medicine, 2009)
The unique demands of exercise and competition can predispose diabetic athletes to harmful complications. A basic understanding of glucose metabolism during exercise, nutritional adequacy, blood glucose control, medications, and management of on-field complications is important for medical personnel who care for diabetic athletes on a daily basis. Diabetic athletes are best managed by "individualized"" preventive and treatment algorithms that should be developed by a team of medical professionals including the athletic trainer, sports nutritionist, and physician.